Listening Comprehension Concerning Mobile Learning In Listen English Daily Practices Application - Ichi Ahada; Iwan Setiawan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2024)
This study aims to evaluate the effectiveness of the Listen English Daily Practices app in enhancing the listening skills of teenage learners at Mulawarman University, East Borneo, Indonesia. This study uses a quasi-experimental method sampling frame using pre-test and post-test. In collecting data, researchers use the listening test as an instrument. The results show that 44% of the participants achieved their goals in accordance with the criteria outlined in the intervention. The study involved 54 students from the English Department who were randomly divided into experimental and control groups. The findings of the hypothesis imply that the use of the Mobile Listen English Daily Practice App improves students' comprehensive understanding of listening skills and could be more widely integrated into English language teaching to enhance students' listening skills.